Effects of Risk Identification Strategy in Supply Chain Operations on the Performance of a National Referral Medical Institution in Nairobi, Kenya - Sakari, Zachary; Chebulobi, Fred; Nyagol, Michael; Otienoh, Ruth; Mukabane, Bonface G (International Journal of Science and Technology, 2019)
A Medical referral institution plays a critical role in the management of health of people in any given country. An interruption in the supply of goods and services to such an institution may lead to inefficiency, ineffectiveness and hence failure to achieve the performance objectives of the medical institution. The objective of the study was to determine the effects of risk identification strategy in supply chain operations on the performance of National Referral Medical Care Institution. The study was carried out at a supply chain management department of the National Referral Hospital in Nairobi County, Kenya. The department deals directly with supply chain operations in the institution. Descriptive research design was adopted while undertaking investigation on the problem. Data was collected using structured questionnaire method. The findings of the study indicated that 90% of the respondents agreed that the institution maintains a risk identification plan while the category of staff involved in risk identification in the supply chain operations was rated at 90% for top management. The types of risks that are most prevalent in the medical institution were rated at 40% for late delivery of medical supplies, 33.3% medical supplies failure, 20% expired medical supplies and 6.7% poor quality of medical supplies. On the factors considered in identification of risks in the supply chain of the institution, desired service delivery and adversity of supply chain risk commanded 40% each. 13.3% indicated frequency of risk occurring and 6.7% showed cost of risk as the factors considered. On the sources of risks in the supply chain for the institution, medical supply stock outs accounted for 30% and expiry of drugs also 30%. Other factors were: high prices, transportation of medical supplies and drug usage all of which scored 40%. On categorization of supply chain risks in the medical institution, the respondents qualified high risk at 43.3%, medium risk level at 36.7% and low risk level at 6.7%. The respondents who did not know accounted for 13.3%. On the frequency of conducting risk identification in the supply chain in the institution, the respondents who were neutral accounted for 33%, those who did know 20%. The respondents who indicated often accounted for 20%, very often were 19% and not often 8%. On the level of risk identification enhancing performance in the institution, 49% of the respondents indicated high performance and 40% were neutral. The study established that risk identification strategy and organizational performance had a positive correlation of 0.141 and 0.458, respectively, on two tail significant level using the Pearson correlation. The researcher recommends that the institution adopts risk identification strategy as basis for risk planning in the supply chain system in order to mitigate both normal and exceptional risks to make supply chain risk management a continuous activity